Online shopping in treatment-seeking patients with buying-shopping disorder - Müller, Astrid; Steins-Loeber, Sabine; Trotzke, Patrick; Vogel, Birte; Georgiadou, Ekaterini; de Zwaan, Martina (Comprehensive Psychiatry, 2019)
Background and aims: With e-commerce becoming an important shopping activity, it has been argued that traditional buying-shopping disorder (BSD) migrates to the online retail market resulting in BSD predominantly online. The aims of the current study were to investigate how many patients with BSD report symptoms of online BSD, and to determine whether symptoms of probable online BSD are related to sociodemographic variables, anxiety, depression, and a higher severity of general BSD. Method: A post hoc analysis of pooled data collected within previous studies (n = 122 treatment-seeking patients with BSD; age Mdn = 42.50, range 20–68 years; 76% women) was conducted. Assessment included the short version of the Internet Addiction Test modified for online shopping sites (s-IATshop), the Pathological Buying Screener (PBS) as an instrument assessing BSD in general, regardless of the buying or shopping environment, and measures for anxiety and depression. Results: 33.6% of the sample met the s-IAT threshold for probable online BSD. Higher s-IAT scores were related to lower age and to a higher severity of anxiety, depression and general BSD. A hierarchical regression analysis with general BSD (PBS score) as dependent variable and partnership status, symptoms of anxiety, depression and online BSD (s-IAT-shop) as predictors indicated a significant positive association of probable online BSD with the severity of general BSD above and beyond anxiety and depression. Conclusion: The findings may encourage future studies addressing phenomenological characteristics, underlying features, associated comorbidity, and clinical relevance of online BSD.
CRIS-Team Scopus Importer:2019-09-20
Keywords: Buying addiction; Compulsive buying-shopping disorder; Internet-use disorder; Online buying-shopping disorder; Pathological buying